Cognitive transfer of Chinese native speakers' use of English quantifiers from the perspective of binomial quantity construction - Yang, YiXuan; Mamat, Roslina Binti (Edelweiss Applied Science and Technology, 2025)
This study aims to explore in depth the cognitive transfer phenomenon among Chinese native speakers in the use of English quantifiers, based on the binomial quantity construction (BQC) theoretical framework. It employs literature review and multimodal empirical research methods to reveal the functional mapping rules of the Chinese quantifier system and its complex impact mechanism on the acquisition of English quantifiers. The research has identified that native Chinese speakers often exhibit systematic errors in using English quantifiers, such as generalized misuse of quantifier selection, mismatched collocations, and improper use of modifiers. These errors primarily originate from cross-linguistic conflicts between the Chinese "numeral+quantifier+noun" structure and the English quantitative expression pattern. The BQC theory effectively explains the mechanism of cognitive transfer by constructing comparative parameters of cross-linguistic quantity structures, providing theoretical support for reducing negative transfer from the mother tongue. In terms of teaching applications, this study proposes a measure word teaching strategy based on BQC theory, which significantly enhances learners' ability to use English measure words through methods such as comparative analysis, practical reinforcement, and classification induction. The experimental results demonstrate that, after receiving teaching interventions guided by BQC theory, learners' accuracy in using quantifiers increased, and the error rates in traditional problem areas such as container quantifiers and set quantifiers decreased significantly. This study not only deepens the understanding of language cognitive transfer phenomena but also offers scientific basis and practical guidance for second language quantifier instruction.